Advocating the rights of people with dementia to contribute to research: Considerations for researchers and ethics committees. (25th November 2021) - O'Connor, Claire M. C.; Liddle, Jacki; O'Reilly, Maria; Meyer, Claudia; Cartwright, Jade; Chisholm, Marita; Conway, Erin; Fielding, Elaine; Fox, Amanda; MacAndrew, Margaret; Schnitker, Linda; Travers, Catherine; et al.
Abstract: Objective: Research involving people with dementia is vital to appropriately inform policy and practice decisions affecting this population. As dementia‐care researchers, we frequently advocate to Human Research Ethics Committees for the right of people with dementia to choose whether to participate in research. This brief report provides some considerations for researchers and ethics committees. Method: Descriptive summary of principles that argue for inclusion of people with dementia in research studies. Results: Specifically excluding people living with dementia from research because of perceived cognitive impairment is inappropriate in light of human rights principles and the right to contribute to evidence‐based care. Conclusions: There is a difference between capacity to provide informed consent and ability to provide perspectives that are valid for each individual. Providing the opportunity for a person with dementia to participate in research and offering support to do this is a matter of human rights.